Employing a knowledge management process in academic and research libraries/ H. Mottaghi-Far - Mottaghi-Far, H. (Fakulti of Information Management, Universiti Teknologi MARA, 2015)
In the 21st century knowledge management is increasing becoming a crucial tool. It has already been successfully implemented in academic libraries. They are the treasure house of knowledge which caters to the needs of scholars, scientists, students and others who are in the mainstream of higher education. Academic libraries are making the transition from traditional centers to modern information ones. These libraries, regarding their necessities, needs and their special conditions should be designed in such a way that they meet the needs and realize the expectations of their patrons best. KM as a managerial task is a process that smooths away and paves the way to this transition and supports a dramatic transformation occurring through operating a thoughtful policy, and with an information technology planning, jointly, brings about a newly-networked and an agreeable environment in academic libraries.